Increased risk of type 2 diabetes among the siblings of patients with schizophrenia. (3rd January 2019) - Huang, Mao-Hsuan; Chen, Mu-Hong; Huang, Kai-Lin; Hsu, Ju-Wei; Bai, Ya-Mei; Cheng, Chih-Ming; Su, Tung-Ping; Li, Cheng-Ta; Tsai, Shih-Jen; Lin, Wei-Chen; Yang, Albert C.; Chen, Tzeng-Ji
Abstract : Background: Research suggests an association between metabolic disorders, such as type 2 diabetes mellitus (T2DM), and schizophrenia. However, the risk of metabolic disorders in the unaffected siblings of patients with schizophrenia remains unclear. Methods: Using the Taiwan National Health Insurance Research Database, 3135 unaffected siblings of schizophrenia probands and 12, 540 age-/sex-matched control subjects were included and followed up to the end of 2011. Individuals who developed metabolic disorders during the follow-up period were identified. Results: The unaffected siblings of schizophrenia probands had a higher prevalence of T2DM (3.4% vs. 2.6%, p = 0.010) than the controls. Logistic regression analyses with the adjustment of demographic data revealed that the unaffected siblings of patients with schizophrenia were more likely to develop T2DM (odds ratio [OR]: 1.39, 95% confidence interval [CI]: 1.10–1.75) later in life compared with the control group. Moreover, only female siblings of schizophrenia probands had an increased risk of hypertension (OR: 1.47, 95% CI: 1.07–2.01) during the follow-up compared with the controls. Discussion: The unaffected siblings, especially sisters, of schizophrenia probands had a higher prevalence of T2DM and hypertension compared with the controls. Our study revealed a familial link between schizophrenia and T2DM in a large sample. Additional studies are required to investigate the shared pathophysiology of schizophrenia and T2DM.